Matemātiskās statistikas un varbūtību teorijas elementi pamatskolā - Kronberga, Tamāra (Latvijas Universitāte, 2011)
Diplomdarbs ”Matemātiskas statistikas un varbūtību teorijas elementi pamatskolā” ir veltīts matemātikas statistikas un varbūtību teorijas stundu izveidei pamatskolas klasēs un satur 6 nodaļas un 5 tabulas. Darba ietvaros pēc autora izstrādātiem kritērijiem ir izpētīti un salīdzināti literatūras avoti par doto tematiku un sniegti 5 matemātikas stundu konspekti, kuri tika aprobēti Ķemeru vidusskolā. Atslēgas vārdi: matemātika, statistika, varbūtību teorija.

The title of Diploma Paper is “The Mathematical probability Theory and Elements of Statistics in Primary School”. This paper is devoted to the lessons in primary school, which are based on mathematical statistics and elements of theory of probability in primary school classes and consists of 6 chapters and 5 basical tables. According to this paper, the analysis of selected literature had been done, by using concrete criterions and ways of discovery, created by the author of Diploma Paper. 5 lesson plans which were tried out during the math lessons in Kemeri secondary school are added as appendicies of the Diploma Paper. Keywords: mathematics, statistics, the theory of probability.
Mathematical statistics and probability theory elements for the elementary school
Keywords: Matemātika